Ответы и объяснения

2013-07-21T12:15:51+04:00
X+y=t
xy=m

m+t=11
mt=30
m=11-t
t(11-t)=30
11t-t^2=30
t^2-11t-30=0
D=121-120=1
t1=(11-1)/2=5
t2=6
x+y=6
x+y=5
x=6-y
x=5-y
m=11-6=5
m=11-5=6
xy=5
xy=6
x+y=6
x+y=5
x=5-y
y(5-y)=6
5y-y^2=6
y^2-5y+6=0
D=25-24=1
y=(5-1)/2=2
y=6/2=3
x=3
x=2
ответ (2;3);(3;2);(1;5);(5;1)



Лучший Ответ!
  • AlbuRin
  • светило науки
2013-07-21T12:37:40+04:00
{x  +  y  +  xy  =  11
{xy*(x  +  y)  =  30
Заменим  х  +  у  =  а,  ху  =  в
{а  +  в  =  11
{а*в  =  30
Это  теорема  Виета    1)    а_1  =  5,  в_1  =  6
                                   2)    а_2  =  6,  и_2  =  5
1)  случай   {x  +  y  =  5
                   {x*y  =  6
Опять   по  теореме  Виета  1)    х_1  = 2       у_1  =  3
                                           2)    х_2  =  3      у_2  =  2
2  случай      {х  +  у  =  6
                    {х*у  =  5
Опять  по  теореме  Виета   1)    х_3  =  1        у_3  =  5
                                           2)    х_4  =  5        у_4  =  1
Ответ.    (1;  5),    (2;  3),    (3;  2),    (5;  1)